Analisis Faktor-Faktor Yang Mempengaruhi Struktur Modal Pada UMKM Toko Favorite Elektronik Furniture Telagasari Karawang - Noval Andriyanto; Enjang Suherman (CV. ITTC INDONESIA, 2024)
The aim of this research is to examine the variables that influence the capital structure of MSMEs in the electronic retail industry. Capital structure is the composition of a company's funding which consists of equity capital and loan capital. This study was carried out by collecting primary data through a survey of a number of electronic shop MSMEs in Telagasari Karawang. Questions in the survey include information about company characteristics, such as company size, age of business, type of ownership, and income level. In addition, external factors such as market conditions, access to funding sources, and government regulations are also part of the analysis. The analytical method used involves multiple linear regression to test the relationship between the independent variables (factors) and the dependent variable (capital structure). Data analysis was carried out using relevant statistical software. It is hoped that the findings of this research will increase knowledge about the variables that influence the capital structure of MSMEs in Telagasari Karawang that operate electronics stores. Business owners can manage their financial structures more effectively by using this knowledge. In addition, the findings of this research can help related organizations and the government formulate policies that can help MSMEs in the electronics industry, such as Telagasari Karawang, in overcoming capital structure obstacles.